Filosofia e poesia: da unidade entre estética e gnosiologia em Friedrich Schlegel - Guilherme Foscolo de Moura Gomes (2010)
The present thesis aims at analyzing the connection established by Friedrich Schlegel between philosophy and poetry theme mainly developed by that author throughout the fragments and texts published in the magazines Lyceum der schönen Künste (1797) and Athenäum (1798-1800). Comprehend the ways through which philosophy and poetry interpenetrate each other in the first Frühromantik writings is fundamental towards understanding the various aspects of Schlegels philosophy particularly, this thesis intends to demonstrate how the option for the apparently unsystematic disposition of the texts conceals an impulse towards its opposite: the only systematization still possible.